Tecnologias digitais na gestão do conhecimento no contexto da gestão de projetos - Gomes, Raimundo José Lopes (2024)
In the competitive context where digital technologies play an increasingly significant role in organisational decisions, it becomes necessary for organisations not only to recognise but also to effectively adapt to technological innovations. This adjustment is particularly relevant when considering knowledge management as an important pillar for supporting strategic decisions and enhancing project management. The ability to integrate new technologies can, therefore, determine positive outcomes in optimising decision-making processes and the successful execution of projects. The appropriate adoption and integration of digital technologies can substantially enhance the efficiency, innovation, and competitiveness of organisations. Thus, developing strategies that promote alignment between digital technologies, knowledge management, and project management is indispensable, creating an environment that fosters the sharing and strategic use of knowledge to reinforce and expand organisational competitiveness in the market. Therefore, the objective of this dissertation is to describe how digital technologies impact knowledge management in the context of project management. To achieve this objective, methodological procedures aligned with a qualitative research approach in two stages were adopted. The first stage involved conducting a Systematic Literature Review (SLR) to understand the theoretical assumptions and research gaps concerning the need to identify how digital technologies affect knowledge management in the context of projects. During the subsequent stage of the investigation, semi-structured interviews were conducted, with a total of twenty interviewees selected, all of whom were project managers. The results of this research are evidenced in the identification of four factors that enable, facilitate, inhibit, or limit the effective integration of digital technologies in knowledge management within the context of project management, thereby transforming the challenges of technological adoption into opportunities for knowledge enhancement and organisational innovation. As a contribution, the guidelines that emerged from this research are presented, aiming to provide useful insights for managers and project leaders. The outlined practical contribution aims not only to facilitate the adoption of digital technologies but also to offer applicable solutions to overcome the challenges encountered, creating a more collaborative and strategically aligned environment for the use of digital technologies in knowledge management within the context of project management. This research is aligned with Research Line 2 (Project Management) linked to the Postgraduate Programme in Project Management – PPGP UNINOVE. The present dissertation is also aligned with other research by its supervisor linked to the core project “People Management and Project Management”.